2003
DOI: 10.1136/vr.153.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Septicaemia and septic arthritis in a neonatal calf caused byLactococcus lactis

Abstract: Differentiation of porcine circovirus I and 2 in formalin-fixed, paraffin-embedded tissues from pigs with postweaning multisystemic wasting syndrome by in-situ hybridisation. Research in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There is no categorization according to the European Pharmacopoeia, and a single dose of 500 mg was found in the German Database. The volatile oil content is described as 2–3% ,, and therefore, each marker in Table was calculated using 1.88 mg. All markers are highly permeable and thus Ginger belongs to BCS class II as some of the mentioned markers, e.g., 8-shogaol and 10- shogaol in Table are poorly soluble and thus belong to class II .…”
Section: Resultsmentioning
confidence: 99%
“…There is no categorization according to the European Pharmacopoeia, and a single dose of 500 mg was found in the German Database. The volatile oil content is described as 2–3% ,, and therefore, each marker in Table was calculated using 1.88 mg. All markers are highly permeable and thus Ginger belongs to BCS class II as some of the mentioned markers, e.g., 8-shogaol and 10- shogaol in Table are poorly soluble and thus belong to class II .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study similarly reported that E. coli made up 51 % of isolates when blood from critically-ill neonatal calves was cultured in the conventional way 7 . Furthermore, E. coli and Lactococcus lactis were determined in septicaemia and septic arthritis in neonatal calves using the same method 26 . In Oxoid Signal blood culture systems, E. coli (65 %) and Group D streptococci (11.5 %) were isolated from the blood of septicaemic calves and foals 11 , while E. coli (56 %) and Actinobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus lactis, recently reclassified as Lactococcus lactis, is not recognized as a common veterinary pathogen, but it has occasionally been reported in the etiology of cattle mastitis and in septic arthritis of the neonatal calf (Wichtel et al 2003). L. lactis is considered to be a skin commensal, and cattle are natural hosts.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…They are often misidentified as entercocci or streptococci, and elucidation of their clinical significance has likely been hindered by the difficulties in correct identification. However, the number of clinical cases associated with infections by L. lactis and L. garvieae has increased in the last decade in both humans and animals (Clark & Burnie 1991, Campell et al 1993, James et al 2000, Wichtel et al 2003.Lactococcus lactis subsp. lactis, L. piscium and L. garvieae are recognized as the species with clinical significance for human and veterinary medicine.…”
mentioning
confidence: 99%